Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3233/jad-2012-120439
|View full text |Cite
|
Sign up to set email alerts
|

Gintonin, a Ginseng-Derived Lysophosphatidic Acid Receptor Ligand, Attenuates Alzheimer's Disease-Related Neuropathies: Involvement of Non-Amyloidogenic Processing

Abstract: Ginseng extracts show cognition-enhancing effects in Alzheimer's disease (AD) patients. However, little is known about the active components and molecular mechanisms of how ginseng exerts its effects. Recently, we isolated a novel lysophosphatidic acid (LPA) receptor-activating ligand from ginseng, gintonin. AD is caused by amyloid-β protein (Aβ) accumulation. Aβ is derived from amyloid-β protein precursors (AβPPs) through the amyloidogenic pathway. In contrast, non-amyloidogenic pathways produce beneficial, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 41 publications
3
121
0
2
Order By: Relevance
“…Gintoninmediated LPA receptor activation is coupled to the increase of soluble amyloid precursor protein α (sAPPα) release instead of β-amyloid in neuroblastoma SH-SY5Y cells. 22) In addition, long-term oral administration of gintonin attenuated neuropathies of β-amyloid plaques in the cortex and hippocampus and restored β-amyloid-induced memory dysfunctions. Third, long-term administration of gintonin to wild-type mice increased the immunoreactivity of hippocampal choline acetyltransferase, which is responsible for increase of acetylcholine synthesis.…”
Section: In Vitro and In Vivo Biological Activities Of Lpas In Foodstmentioning
confidence: 99%
See 1 more Smart Citation
“…Gintoninmediated LPA receptor activation is coupled to the increase of soluble amyloid precursor protein α (sAPPα) release instead of β-amyloid in neuroblastoma SH-SY5Y cells. 22) In addition, long-term oral administration of gintonin attenuated neuropathies of β-amyloid plaques in the cortex and hippocampus and restored β-amyloid-induced memory dysfunctions. Third, long-term administration of gintonin to wild-type mice increased the immunoreactivity of hippocampal choline acetyltransferase, which is responsible for increase of acetylcholine synthesis.…”
Section: In Vitro and In Vivo Biological Activities Of Lpas In Foodstmentioning
confidence: 99%
“…23) Thus, LPAs in gintonin contributed to the restoration of adult brain cholinergic dysfunctions following neurodegeneration. 22) Fourth, Kim et al observed that hippocampal long-term potentiation (LTP) increased in mice that were previously treated with gintonin for 7 d orally compared to saline-treated mice. 24) In addition, the hippocampi of mice that were previously treated for 7 d with gintonin showed increased expressions of learning and memory-related proteins such as phosphorylated cAMP-response element binding (pCREB) protein and brain-derived neurotrophic factor (BDNF).…”
Section: In Vitro and In Vivo Biological Activities Of Lpas In Foodstmentioning
confidence: 99%
“…sient is coupled to important pharmacological effects, such as the attenuation of amyloid plaque formation in the brain. 7,13) In addition, gintonin inhibits autotaxin activity to suppress metastasis. 8) However, a method for quantifying the amount of gintonin in ginseng has not been developed.…”
Section: Detection Of Gintonin In Ginseng Productsmentioning
confidence: 99%
“…2,3,5,6) The gintonin-mediated [Ca 2+ ] i transient is coupled to the regulation of Ca 2,7) Oral administration of gintonin elicits anti-Alzheimer's disease effects in vivo by activating the non-amyloidogenic pathway through LPA receptors and induces anti-metastatic effects by inhibiting autotaxin activity. 7,8) Biochemical analysis has shown that gintonin consists of carbohydrates, lipids, and proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation